Quantifying grain storage structure leakage by testing effects of environmental conditions on pressure loss - Jones, Carol; Conley, Taylor (Julius-Kühn-Archiv, 2018)
A major concern in grain storage and management facilities is the effective control of insects and pests that reside in stored grain. Currently, the best studied method of subduing these insects is fumigating the grain bins with phosphine. However, many grain storage insects have developed a resistance to phosphine due to its misuse over the years, partially due to bin leakage, leading to minimum pest control in grain and increased product damage. The first step in managing the issue of fumigant leakage is by identifying environmental conditions that may impact the bins’ total air loss, and ultimately, fumigant loss. One way to quantify the leakage potential of a structure is to perform pressure tests. Data collected from these tests statistically quantify the significance of atmospheric conditions on bin leakage, as well as quantify leakage area in the bin. These tests were performed on a 500 bushel grain bin filled with canola seed, sealed with plastic sheeting and Gorilla duct tape. A PVC pipe “arm” and shop vacuum (Shop-Vac® 5-gallon 6-Peak HP) contraption was designed for pressure application. Constant pressure testing methods were performed to collect data for calculations of leakage area. Tests were repeated in varying environmental conditions. Data analysis included performing single sample ttests to determine significance of environmental conditions, as well as using previously established relationships to quantify predicted leakage area in each scenario. It was concluded that atmospheric conditions significantly affect gas leakage from structures (p < 0.001), so pressure test conditions should match fumigation conditions for an accurate initial fumigant dosage. Constant pressure tests accurately predict equivalent leakage area of bin, with areas demonstrating a variance of 3.4 x 10-5. Future tests to improve fumigating processes could include relationships between phosphine concentration and the leakiness of the bin, as well as automated constant pressure testing devices.